Analisis Audit Sistem Informasi Creative Banking Nusantara pada PT BPR Dana Bintan Sejahtera Menggunakan COBIT 5 - Dwi Nurul Huda; Darwin, Darwin (Jurnal Bangkit Indonesia, 2024)
The Creative Banking Nusantara application is a banking application released by PT BPR Dana Bintan Sejahtera and is used to carry out customers' daily banking transactions. Currently, the Creative Banking Nusantara application has never had an information technology governance audit conducted to determine the capability level and rating scale of the Creative Banking Nusantara application. This research aims to find out the extent to which information technology governance has been implemented by PT BPR Dana Bintan Sejahtera, and whether it has met expectations or not. This research will provide recommendations if the assessment results do not meet the company's expected achievement targets. This research will audit the Creative Banking Nusantara application using COBIT 5 with the delivery, service, and support domains (DSS). In collecting data, this research used a questionnaire technique with the selection of respondents using a purposive sampling technique while testing the validity of the questionnaire using SPSS. This research produces an analysis using the COBIT 5 framework and concludes that the average capability level assessment using the COBIT 5 framework is at a value of 4.29 or 4, namely at the predictable process level, while the average rating scale assessment is 89.24. % or has reached Level F, namely Fully Archived.